Optically Stimulated Luminescence (OSL) dating of sand‐filled wedge structures and their fine‐grained host sediment from Jonzac, SW France. (25th July 2012) - Guhl, Anja; Bertran, Pascal; Zielhofer, Christoph; Fitzsimmons, Kathryn E.
<x xml:space="preserve">Abstract</x> Two sand wedge structures and their host sediments, from Jonzac in SW France, were successfully dated using Optically Stimulated Luminescence (OSL) measurements on both small aliquots and single grains of quartz from the 180–212 μm size fraction. One of the sand wedges clearly contains primary infilling. However, grain‐size analysis and field observations do not clearly indicate whether the other feature represents a primary sand wedge or a composite sand wedge with primary and secondary infilling. OSL results and the geological setting justify using the Central Age Model (CAM) for the calculation of age estimates. Grain‐size analysis and detailed investigations of OSL results revealed the contamination of one sand wedge sample with host sediment. However, age calculation using the Finite Mixture Model (FMM) provided what is considered to be a reliable age estimate for the contaminated sample. The age estimates for all samples correspond to Marine Isotope Stage (MIS) 3. While fine‐grained sediments were deposited in the middle of MIS 3 (c. 43–55 ka), the sand wedges unexpectedly correspond to the end of this period (c. 33 ka) or the onset of MIS 2 (c. 27 ka). The sand wedges were probably formed during intense but short cold periods, possibly correlated with a Heinrich event (H2 and/or H3). The results help us to assess how effective luminescence dating is on sand wedges and the limitations involved in correlating sand wedge ages with Heinrich events, and contribute to the debate on the timing of cryogenic formation processes and the permafrost distribution in SW France.